2017
DOI: 10.1371/journal.pone.0178869
|View full text |Cite
|
Sign up to set email alerts
|

Low pH reduces the virulence of black band disease on Orbicella faveolata

Abstract: Black band is a deadly coral disease found worldwide, which may become more virulent as oceanic conditions continue to change. To determine the effects of climate change and ocean acidification on black band disease virulence, Orbicella faveolata corals with black band were exposed to different temperature and pH conditions. Results showed a significant decrease in disease progression under low pH (7.7) conditions. Low pH also altered the relative abundance of the bacterial community of the black band disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…It has further been suggested that other anthropogenic activities, such as coastal pollution or ocean acidification, contribute to the increase of coral disease incidents ( Jackson et al, 2001 ; Muller et al, 2017 ; Rosenberg & Ben-Haim, 2002 ). The surveyed outbreak area was adjacent to the outflow of a large aquaculture facility, which might have further aggravated the effects of the bleaching event due to increased nutrient availability ( Roder et al, 2015 ; Ziegler et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has further been suggested that other anthropogenic activities, such as coastal pollution or ocean acidification, contribute to the increase of coral disease incidents ( Jackson et al, 2001 ; Muller et al, 2017 ; Rosenberg & Ben-Haim, 2002 ). The surveyed outbreak area was adjacent to the outflow of a large aquaculture facility, which might have further aggravated the effects of the bleaching event due to increased nutrient availability ( Roder et al, 2015 ; Ziegler et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Ruegeria had different patterns once it was the most abundant genera in diseased colonies. This genus is known to be associated with several healthy 14 , 59 61 and diseased zooxanthellate corals 10 , 11 , 14 , 22 24 . Previous studies suggested that Ruegeria inhibits/controls the growth of other bacteria genera through tropodithietic acid 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge about coral disease interactions with environmental stressful conditions can also be widely expanded if we increase the attention to other variables or their interactions with some better studied ones. The role of high temperatures has been the main environmental driver addressed, in coral research, however there are other conditions that have been explored in a few papers like changes in water pH (Muller et al., 2017; Stanić et al., 2011; Remily & Richardson, 2006), dissolved oxygen (Remily & Richardson, 2006), and other better studied like the role of nutrient enrichment (Kaczmarsky & Richardson, 2011; Vega-Thurber et al., 2014; Voss & Richardson, 2006; Bruno et al., 2003; Looney, Sutherland & Lipp, 2010) whose potentially interactive effects with temperature and diseases remain far less explored.…”
Section: Discussionmentioning
confidence: 99%